Dynamics of rheological properties of oral fluid in the course of their correction in patients with diabetes who use removable complete denture (RCD) - Лейбюк, Любов Василівна (Actual Dentistry, 2020)
Summary. Diabetes is a chronic disease that influences on all types of metabolism in the human body: carbohydrate, fat and protein. Typically, the clinical changes in the oral cavity are often the first manifestations of diabetes, which is important diagnostic value. In patients with diabetes the clinical and laboratory parameters are different comparing with persons without somatic pathology such as: dryness and pastosity of the mucous membrane of the oral cavity, hyposalivation, which leads to an increase in dental plaque; increase in total fibrinolytic activity of the oral fluid; increased bleeding gums. According to the professional literature, diabetes significantly increases the risk of development periodontitis, affects the intensity and degree of destruction of the periodontal structures, which, in turn, leads to loss of teeth and deterioration of living standards of such patients. Decreased salivation is significantly complicating the prosthodontics of patients with diabetes who have complete loss of teeth. There is the longest adaptation to removable prostheses in patients with reduced rates of salivation. Adaptive processes to RCD are known to be influenced by the main rheological properties of the oral fluid: salivary velocity, oral fluid viscosity, and pH. The purpose. The aim of our study was to evaluate the effectiveness of correction of complications in prosthodontics with removable complete denture at patients with diabetes of type II, according to the dynamics of rheological properties of the oral fluid. Materials and methods. Patients with diabetes of type II who have removable complete denture were divided into two groups: the main group (52 patients) and the control group (52 patients). The patients of the main group were treated according to the developed treatment-and-preventive scheme, which included the general prescriptions (vitamin-mineralcomplex «Alphabet Diabetes») and the local therapeutic measures (anti-inflammatory elixir «Lizomucoid», gel «Dentaid Xeros»). Patients from the control group were prescribed treatment according to the standard method. Results. After one month application of the proposed treatment-and-preventive scheme, salivation rate increased by 1.9 times, the viscosity of the oral fluid decreased by 1.2 times, the value of the pH increased from 5.94±0.48 to 6.77±0.55 at the patients of the main group comparing before treatment (p < 0.01). In the long-term following at the main group (12 months later), salivation rate was 0.36±0.04 ml/min, which was 1.3 times higher than before treatment; oral fluid became less viscous by 1.1 times; the pH value of 6.38±0.39 was within the physiological norm and was significantly higher comparing the value before treatment by 1.07 times. The positive dynamics of the rheological properties of the oral fluid was observed only after one month at the patients the control group. Conclusion. Correction of rheological properties of the oral fluid with the developed treatment regimen both in the immediate and long term observation significantly improved the clinical condition of the oral cavity of the patients of the main group compared to the control group who had inflammatory phenomena and mucosal dryness. Objective examination data were supplemented by patients’ subjective evidence of increased salivation as a result of pathogenetic therapy. Key words: diabetes, removable complete denture (RCD), rheological properties of oral fluid.